THE INFLUENCE OF PRODUCT KNOWLEDGE, TRUST AND SOCIALIZATION ON CUSTOMER DECISIONS IN FINANCING "FUTURE PACKAGE" AT BTPN SYARIAH (STUDY AT BTPN SYARIAH MMS BANKING MOJOSONGO, BOYOLALI, INDONESIA) - Cindy Madiyaningsih; Prastiwi, Iin Emy; Muhammad Tho’in (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Future Package Financing is an integrated program of Bank BTPN Syariah given to a group of woman in rural areas who want to own a business and have dreams of changing their lives, but do not have access to banking service. The main goal is to provide financial solution, simple financial solutions, simple financial planning and group participation. Marketing financing is carried out through MMS (Mobile Marketing Syariah), namely branch offices located in sub-districts. This research uses three variables, namely independent product knowledge trust and socialization with one dependent variable, namely decision to finance. Menwhile, the sample used was 100 respondents obtained using the simple random sampling method. The data analysis method used is quantitative anlysis, namely validity and reliability tests, classical assumption test, multiple regressuin analysis, t test, F test and coefficient of determination (R2). Based on data analysis, the research results sho that the indicators in this research are valid and reliable. In the classical assumption test, the data is normally distributes, heteroscedasticity and multicollinearity do not occur. The t test dhows that the variables product knowledge, trust and socialization have a significant effect on the decision to finance PMD. From the statistical results of the F test, it is known that product knowledge, trust and socialization jointly influence the decision to finance PMD. In the test, it is known that the coefficient of determination (R2) shows that product knowledge, trust and socialization can influence customer decision by 69,5% while 30,5% is influenced by other factors outside this research. Keywords: Product Knowledge, Trust, Socialization, Future Package Financing (PMD) And Decision To Make Financing